An Analysis of Village Fund Implementation in Central Java Province: An Institutional Theory Approach With a Modeling Institutional Aspect - Eko Nur Surachman (Indonesian Treasury Review: Jurnal Perbendaharaan, Keuangan Negara dan Kebijakan Publik, 2020)
The implementation of the fiscal decentralization concept in Indonesia has completed with the issuance of the Village Law and Village Fund Program. Nevertheless, some problems arose in the application. This study aims to map the issues and to build a relationship model based on institutional theory, using content analysis and triangle approach interviews. The study concludes that the Village Fund is profoundly affected by the coercive element that is sourced from the authority of the government to regulate and supervise the program. The coercive then influence the normative in which the regulation frame and strict implementation lead to the difficulties to fulfill the administrative requirements. It then affects the cognitive element on how to make sustain and executable planning of the Village Fund Program, which leads to poor planning, so that difficult to be executed. As it is mandatory, the program is still run improvised that makes the output utilization was low.